(untitled) (Scientific journal of the Fergana State University, 2026)
The article analyzes foreign innovations in protection against debris flows and floods based on key scientific and patent sources from 2010-2024. A shift from traditional infrastructure to integrated systems is identified, which include monitoring, risk-informed design, and flexible modular barriers. Key trends include systemic risk management, data-centricity, probabilistic design, and technological advancement. The necessity of a comprehensive, science-based approach to risk reduction is substantiated.